Hypertension and dietary patterns of the adult population. Results of the Russian epidemiological study ESSE-RF - N. S. Karamnova; S. A. Maksimov; S. A. Shalnova; Yu. A. Balanova; S. E. Evstifeeva; А. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; O. B. Shvabskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To study the associations of dietary patterns with HTN in the adult population.Material and methods. The analysis was carried out on the data of representative samples of male and female population from 13 regions of Russia. The age ranged from 25 to 64 years (n=19,520; men, 7329; women, 12191). The response rate was approximately 80%.Results. Men with blood pressure (BP) >140/90 mm Hg more often consume meat and sausage products (OR, 1,08 [95% CI, 1,02-1,16]; p=0,011), less often — fresh vegetables/fruits (0,94 [0.89-0.96]; p=0,028), dairy products: milk, kefir (0,92 [0,87-0,97]; p=0,0041), sour cream (0,90 [0,84-0,96]; p=0,0021), cottage cheese (0,92 [0,85-0,99]; p=0,034) and sweets (0,91 [0,86-0,96]; p=0,00071). Women with BP >140/90 mm Hg less often consume fresh vegetables/fruits (0,95 [0,90-0,99]; p=0,032), milk, kefir (0,95 [0,91-0,99]; p=0,040), cottage cheese (0,95 [0,90-0,99]; p=0,047), cheese (0,92 [0,88-0,97]; p=0,00083) and sweets (0,89 [0,850,93]; p<0,00001). Persons with HTN more often consume fish products, fresh vegetables/fruits, less often — sweets, sugar and dairy products. Consumption of meat and sausage products does not differ in persons with/without HTN, as well as the habit of adding more salt. People taking antihypertensive medications (AHM) consume less salt. Men consume pickles less often, but not meat and sausage products; excess salt intake decreased (0,90 [0,83-0,98]; p=0,018). Women taking AHM consume meat and sausage products, but without affecting the salt level in diet. In persons taking AHM: among men (by 13%) and among women (by 10%), the consumption of fresh vegetables/fruits is higher and sugar — lower. Among people taking AGHM the cardioprotective type of diet is more common: by 12% among women and by 33% among men; a healthy diet is more common (by 29%) only among men. Women taking AHM and not reaching the target BP more often consume meat and sausage products (1,14; [1,06-1,22]; p=0,00044), and men — high-fat dairy products (1,20 [1,03-1,39]; p=0,022).Conclusion. People with hypertension are more likely to consume vegetables/fruits than those without hypertension, but the intake of high-sodium foods remains unchanged.